[Selections from West Africa Mission letter book] - Church Missionary Society West Africa Mission; University of Birmingham Library; Church Mission Society; Adam Matthew Digital (Adam Matthew Digital, 2007)
Selections from the ms. letter books of the Church Missionary Society's West Africa Mission relating to the founding of a boys' grammar school, Fourah Bay College, at Freetown (1st sequence) and to the founding of a girls' school in Freetown (2nd sequence)